Gadolinium-Based Nanoparticles for Theranostic MRI-Guided Radiosensitization in Hepatocellular Carcinoma - Hu, Pengcheng; Fu, Zhequan; Liu, Guobing; Tan, Hui; Xiao, Jie; Shi, Hongcheng; Cheng, Dengfeng (Frontiers in Bioengineering and Biotechnology, 2019)
Background: Radiation therapy (RT) of hepatocellular carcinoma (HCC) is limited by low tolerance of the liver to radiation. Radiosensitizers can effectively reduce the required radiation dose. Multimodality gadolinium-based nanoparticles (AGuIX) are small and have enhanced permeability and retention effects; thus, they are very suitable for radiation sensitizer HCC RT. Here, we evaluated the potential value of AGuIX for theranostic MRI-radiosensitization in HCC. Methods: The radiosensitization effects of AGuIX were evaluated via in vitro and in vivo experiments. Tumor growth, apoptosis imaging, and immunohistochemistry were performed to verify the antitumor effects of RT with AGuIX. Results: In vitro evaluation of the efficacy of radiosensitivity of the AGuIX demonstrated that the presence of AGuIX significantly decreased HepG2 cell survival when combined with an X-ray beam. In vivo MRI imaging showed the ratio of tumor/liver concentration of the AGuIX was the highest 1 h after intravenous injection. For antitumor effects, we found that the tumor size decreased by RT-only and RT with AGuIX. The antitumor effects were more effective with high-dose AGuIX-mediated RT. Apoptosis imaging and immunohistochemistry both demonstrated that the degree of the cell apoptosis was highest with a high dose of AGuIX-mediated RT. Conclusions: This study provides compelling data that AGuIX can facilitate theranostic MRI-radiosensitization in HCC.